Constructing the value, ownership, and consumption of virtual goods from an Islamic economic perspective - Muhammad Fajar Noor Khamdani; Muhammad Royhan (Novera: Journal of Economics and Business, 2026)
The emergence of virtual goods has created a new form of consumption involving real economic expenditure on intangible digital objects, while studies specifically constructing virtual goods consumption from an Islamic economic perspective remain limited. This study aims to construct a concept of virtual goods consumption based on Islamic economic principles. A qualitative conceptual approach was employed through thematic analysis of literature on virtual goods, virtual economy, and Islamic consumption. The findings demonstrate that virtual goods consumption should be evaluated through needs, maṣlaḥah, rationality, financial capacity, proportionality, and the limits of isrāf and tabdhīr, rather than solely through economic value or consumer satisfaction. The study proposes responsible virtual consumption as a conceptual framework integrating digital benefits, financial capacity, and wasatiyyah. This framework extends Islamic economic discourse into digital consumption and provides a conceptual basis for assessing the appropriateness of expenditure on virtual objects. Abstrak Perkembangan virtual goods telah menciptakan bentuk konsumsi baru yang melibatkan pengeluaran ekonomi nyata untuk memperoleh objek nonfisik, sementara kajian yang secara khusus mengonstruksi konsumsi virtual goods dalam perspektif ekonomi Islam masih terbatas. Penelitian ini bertujuan mengonstruksi konsep konsumsi virtual goods berdasarkan prinsip ekonomi Islam. Penelitian menggunakan pendekatan kualitatif dengan desain studi konseptual melalui analisis tematik terhadap literatur mengenai virtual goods, virtual economy, dan konsumsi Islam. Hasil penelitian menunjukkan bahwa konsumsi virtual goods perlu dinilai melalui kebutuhan, maṣlaḥah, rasionalitas, kemampuan ekonomi, proporsionalitas, serta batas isrāf dan tabdhīr, bukan semata-mata berdasarkan nilai ekonomi atau kepuasan pengguna. Penelitian ini menghasilkan konsep responsible virtual consumption sebagai konstruksi konsumsi virtual yang mengintegrasikan manfaat digital, kemampuan ekonomi, dan prinsip wasatiyyah. Konsep tersebut memperluas kajian ekonomi Islam ke ranah konsumsi digital dan memberikan dasar konseptual untuk menilai kewajaran pengeluaran atas objek virtual.